2022
DOI: 10.3390/pharmaceutics14122749
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Biofabrication Technologies and Cell Therapies for Wound Healing

Abstract: Background: Cell therapy holds great promise for cutaneous wound treatment but presents practical and clinical challenges, mainly related to the lack of a supportive and inductive microenvironment for cells after transplantation. Main: This review delineates the challenges and opportunities in cell therapies for acute and chronic wounds and highlights the contribution of biofabricated matrices to skin reconstruction. The complexity of the wound healing process necessitates the development of matrices with prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…[ 330 ] This requires the development and integration of advanced fabrication systems to model the full complexity of atherosclerosis. [ 331 , 332 ] A recent study demonstrated the multimodal fabrication principle in atherosclerosis by combining volumetric bioprinting with melt electrowriting to create stenosed vessels with physiologically relevant mechanical properties. [ 316 ] Multimodal approaches will allow tuning of the vessel properties to match the changes in the mechanical properties of the vessel wall and plaque associated with atherosclerosis progression, ultimately improving the utility of tissue‐engineered and biofabricated models.…”
Section: Critical Outlook and Future Directionsmentioning
confidence: 99%
“…[ 330 ] This requires the development and integration of advanced fabrication systems to model the full complexity of atherosclerosis. [ 331 , 332 ] A recent study demonstrated the multimodal fabrication principle in atherosclerosis by combining volumetric bioprinting with melt electrowriting to create stenosed vessels with physiologically relevant mechanical properties. [ 316 ] Multimodal approaches will allow tuning of the vessel properties to match the changes in the mechanical properties of the vessel wall and plaque associated with atherosclerosis progression, ultimately improving the utility of tissue‐engineered and biofabricated models.…”
Section: Critical Outlook and Future Directionsmentioning
confidence: 99%
“…92 The advancements in scaffold fabrication techniques (e.g., melt electrowriting, and (3D) printing) enabled the development of structures with advanced architectures. 93,94 The electrospinning technique is one of the approaches for scaffold fabrication due to its capacity to resemble the fibrous structure of ECM. Electrospun products have been widely used to develop wound dressing substrates.…”
Section: Reviewmentioning
confidence: 99%
“…, melt electrowriting, and (3D) printing) enabled the development of structures with advanced architectures. 93,94…”
Section: Regenerative Approaches To Indue Skin Innervationmentioning
confidence: 99%